Analysis of the advantages of playing at home in male Brazilian volleyball - Angioluci Diniz Campos, F.; Natale Pasquarelli, B.; Benetti Campos, L. C.; Heidi Ozaki, E.; Reeberg Stanganelli, L. C. (Brazilian Journal of Biomotricity, 2013)
This study was to investigate the advantage of playing at home in men's volleyball and its influence on performance indicators, in the game score. The sample consisted of 132 men's national games of Brazilian league (from the 2012/2013 season), with 525 sets and 23,820 points in total. The relationship of performance indicators with the game outcome (win or lose) was assessed including: serve, attack, block and opponent`s error. The results showed that the there was a home advantage effect in men volleyball league, with a higher prevalence of victory for the home teams (56,1%). Among the aspects that were most highly correlated with victory, the attack and block stands out as the technical indicator that defines most of results of volleyball games.